Determining the welfare of the child in custody adjudication in Malaysia: an appraisal / Osart Jallong - Jallong, Osart (Faculty of Law, 1982)
The most important principle which a court in Malaysia has to apply in determining a custody case is that the welfare of the child is primary or paramount. No doubt, the welfare of the child as a concept has gained world-wide acceptance. But what exactly does it require is not very dear* Legislatures, the courts and experts from related disciplines where the children's welfare are their concern have, at various times, attempted to provide content to it, or at least laid down some broad guidelines upon which the courts may make their decisions. Considerable development has taken place in this area of the law. What are the reactions of the Malaysian courts and legislature to all these? How did the courts apply and define the concept? From an analysis of the decided cases, several conclusions are made, out of which are the courts* tendency to take into account the conduct of the parents, the "tenderyears presumption” and the wishes of the child, as some of the factors in determining the child's welfare.